The hieros logos of Israelite circumcision in light of the text history of Josh 5,4-6: a study of intertwined textual and literary criticism - Schenker, Adrian (Semitica et Classica, 2015)
Abstract The Masoretic and the Old Greek Bible do not explain in the same way the reason for the circumcision of the Israelites at the threshold of the Promised Land in Josh 5,2-9. The explanation of this difference is disputed since more than a century. The solution suggested here combines textual and literary criticism. The earliest form of the text which may thus be established opens access to a specific tradition on the origins of circumcision which differs from that of Genesis 17. Abstract La raison de la circoncision des Israélites au seuil de la Terre promise en Jos 5,2-9 n’est pas la même dans la Bible massorétique et dans la Bible grecque ancienne. L’explication de cette différence est controversée depuis plus d’un siècle. La solution suggérée ici combine critique textuelle et critique littéraire. La forme la plus ancienne du texte ainsi retrouvée donne accès à une tradition spécifique de l’origine de la circoncision israélite, différente de celle de Genèse 17.